CHANGES OF LAND USE MONITORING WITHIN FOREST AREA - Pribadi, Cherie Bhekti; Hariyanto, Teguh; Kurniawan, Akbar; Amriana, Yessherly (Geoid, 2019)
Pasrujambe District is one of sub-districts in Lumajang Regency which has a forest area. Forests are main source of life for people who live in surrounding villages, start from farming, logging, taking firewood, gathering, and grazing their livestock in forest areas. This phenomenon cannot be avoided from use of forest land for the other land functions, both for settlements, agriculture and other regions. Therefore, it’s needed to be related to changes of land use in forest areas. In this study an evaluation of distribution and extent of land use functions in Pasrujambe District forest area was carried out using 2 (two) methods, namely object-based classification methods and interpretation methods (digitized on screen). The results show us that there are changes of land use in forest areas in 2017, such as industries, plantations, agricultures, plantations, bushes and settlements with total area of 3764.38 Ha and for agricultural land use such as lakes, grasslands and rivers with total area of 799.41 ha